2012
DOI: 10.2174/092986712803251539
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Mass Spectrometry Newborn Screening for Inborn Errors of Intermediary Metabolism: Abnormal Profile Interpretation

Abstract: Expanded newborn screening for inherited metabolic disorders using tandem mass spectrometry was introduced in 1990's and is widely used around the world. In contrast to conventional screening methods, tandem mass spectrometry does not measure single analytes but identifies and quantifies metabolite profiles; one single blood spot analyzed provides information of about 60 metabolites including amino acids, acylcarnitines and related ratios that enable the diagnosis of approximately 50 different diseases. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
(178 reference statements)
0
14
0
1
Order By: Relevance
“…An example of diagnosis of pre- and a-symptomatic diseases is represented by the targeted metabolomic approach applied to newborn screening for inherited metabolic disorders. The IEMs including OAs were diagnosed by using tandem mass spectrometry since the 1990s [ 42 , 43 ]. More than 70 different metabolic diseases can be diagnosed by measuring metabolites extracted from a single dried blood spot (DBS) collected within 48–72 hours of birth.…”
Section: Metabolomic Strategies and Applications In Organic Acidemmentioning
confidence: 99%
“…An example of diagnosis of pre- and a-symptomatic diseases is represented by the targeted metabolomic approach applied to newborn screening for inherited metabolic disorders. The IEMs including OAs were diagnosed by using tandem mass spectrometry since the 1990s [ 42 , 43 ]. More than 70 different metabolic diseases can be diagnosed by measuring metabolites extracted from a single dried blood spot (DBS) collected within 48–72 hours of birth.…”
Section: Metabolomic Strategies and Applications In Organic Acidemmentioning
confidence: 99%
“…Impaired acylcarnitines profile not only may be a consequence of inherited metabolic diseases (IMD), but also might be the reflection of different pathologies such as sepsis, malnutrition, type I and II diabetes, obesity, and intrauterine growth restriction. [16] This versatility is due to the fact that the free hydroxyl group of LC—a semi-essential nutrient for the newborn [79] —can react with a wide range of molecules resulting in a broad spectrum of molecule structures, and in its capability to transfer esterified metabolites. [10]…”
Section: Introductionmentioning
confidence: 99%
“…This results in an increase in urine levels of glutaric acid and 3-hydroxy-glutaric acid (1). It has been reported that the incidence rate of GA-I is ~1:100,000 (2). Approximately 90% of patients develop GA-I in early childhood, and the remaining 10% of patients show mild symptoms or no symptoms (3).…”
Section: Introductionmentioning
confidence: 99%